Unveiling Lessons from Volvo’s Post-Merger Integrations: Enhancing Future Processes A Multiple Case Analysis for Successful Post-Merger Integrations - Back, Hampus; Jönsson, Albin (My University, 2023)
Background: Mergers and acquisitions have surged in popularity as a strategy for corporate growth. However, the majority of M&A deals fail to achieve their objectives. This thesis examines AB Volvo, a company that have achieved long-lasting success through strategic acquisitions emphasized at maintaining independent operations, to identify learnings connected to their post-merger integration processes. Purpose: To analyse Volvo’s essential, historical factors for a successful post-merger integration, aiming to improve future integration processes. Problem: To remain competitive, it is increasingly important to accelerate to- wards more sustainable products. M&A is a crucial tool to successfully drive current business performance and the transformation to meet future demands simultaneously. Additionally, to achieve the strategic intent the integration processes is identified to be especially important. However, considering the complexity and contingencies of post-merger integration, it is difficult to create a framework that can be applied to all M&A transactions. Hence, firms must learn from previous experiences to their PMI process. By providing learnings from earlier acquisitions, this thesis will contribute to knowledge and capabilities needed for successful post-merger integrations. Theoretical framework: The thesis was conducted as a case study, where Volvo’s post-merger integration process was examined. Two main sources of data were used to lay a foundation for the thesis. The first one was a literature study, where existing knowledge from the research area was combined. The second source of data was semi-structured interviews which was conducted with relevant professionals involved in two earlier acquisitions. Frameworks and insights from the literature study were applied to empirical findings to form the analysis and draw conclusions. Findings and recommendations: The thesis examines several aspects of Volvo’s strategical and sociocultural processes and reveals successful practices as well as areas of potential improvements. These are both based on existing literature but also through patterns visible in the cases.
Keywords: Post-merger integration; Post-acquisition integration; M&A; Structural integration; Sociocultural integration; Change management; Strategy implementation; Organisational change